Alteration of the murine gut microbiota during infection with the parasitic helminth, Heligmosomoides polygyrus - Walk, Seth T. (2010)
In a murine model of inflammatory bowel disease (IBD), treatment of colitis in IL-10 gene deficient mice with the parasitic helminth, Heligmosomoides polygyrus, ameliorates colonic inflammation. The cellular and molecular mechanisms driving this therapeutic host response are being studied vigorously. One proposed mechanism is that H. polygyrus infection favors the outgrowth or suppression of certain bacteria, which in turn help modulate host immunity. To begin to address this hypothesis, we quantified the effect of H. polygyrus treatment on the composition of the gastrointestinal (GI) tract microbiota in the absence of inflammation, using wild-type C57BL/6 mice. Here, we present evidence that a significant shift in the abundance and relative distribution of bacterial species in the ileum of mice is associated with H. polygyrus infection. Members of the bacterial family, Lactobacillaceae, significantly increased in abundance in the ileum of infected mice reproducibly in two independent experiments despite having different microbiotas present at the outset of each experiment. These data support the concept that helminth infection shifts the composition of intestinal bacteria. The clinical consequences of these shifts in intestinal flora are yet to be explored.